Healthy Living in Islam: The Principle of Halal and Its Implications for Health - Astiwara, Endy Muhammad (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This study explores the concept of halalan tayyiban as a holistic Islamic framework for healthy living, emphasizing its implications for physical, mental, and spiritual well-being. Grounded in a descriptive qualitative methodology, the research draws upon religious texts (Qur'an, Hadith), fatwas, and public health policy documents to analyze how halal principles shape lifestyle practices among Muslims. The findings indicate that adherence to halal principles, such as the consumption of clean, safe, and permissible food and medicine, not only reduces the risk of non-communicable diseases but also fosters psychological peace and spiritual fulfillment. Comparative insights reveal that, unlike secular health paradigms or lifestyle diets (e.g., veganism), the halal framework integrates health with ethical and spiritual responsibilities. The study also addresses key challenges in implementing halal standards, including public awareness gaps, the complexity of halal supply chains, and ambiguities in multinational product labeling. The halal lifestyle offers a viable model for improving public health in Muslim-majority and minority settings by aligning with WHO's preventive health strategies. The research underscores the need for stronger collaboration between religious authorities, health institutions, and the global halal industry to ensure sustainable implementation.